Objective molecular dynamics - Dumitrică, Traian; James, Richard D. (Journal of the mechanics and physics of solids, 2007)
We introduce a generalization of periodic molecular dynamics that we term objective molecular dynamics. It is a method of doing molecular dynamics for a restricted set of atoms, nonperiodically mapping the time-dependent displacements of this small set of atoms onto the full, typically infinite structure, such that the full structure satisfies exactly the full, unconstrained set of equations of molecular dynamics subject to certain group-invariant initial conditions. The method is applicable to a wide variety of interesting molecular structures including the tails, capsids and other parts of many viruses, carbon nanotubes, many of the common proteins, C 60 and many other nanostructures now being synthesized, especially via the process of self-assembly. The method is illustrated by simulations of carbon nanotubes.